Roles of NPAS2 in circadian rhythm and disease. (20th August 2021) - Peng, L u; Bai, Gaigai; Pang, Yingxin
Abstract: NPAS2, a circadian rhythm gene encoding the neuronal PAS domain protein 2 (NPAS2), has received widespread attention because of its complex functions in cells and diverse roles in disease progression, especially tumorigenesis. NPAS2 binds with DNA at E-box sequences and forms heterodimers with another circadian protein, brain and muscle ARNT-like protein 1 (BMAL1). Nucleotide variations of the NPAS2 gene have been shown to influence the overall survival and risk of death of cancer patients, and differential expression of NPAS2 has been linked to patient outcomes in breast cancer, lung cancer, non-Hodgkin's lymphoma, and other diseases. Here, we review the latest advances in our understanding of NPAS2 with the aim of drawing attention to its potential clinical applications and prospects.